Bioactivity-directed isolation of antisickling compounds from Cnidoscolus acontifolius (Mill.) I.M. Johnst leaf extract - Mojisola C. Cyril-Olutayo; Temitope A. Adeyemo; Ayodeji O. Oriola; Joseph M. Agbedahunsi (Journal of Pharmacy & Pharmacognosy Research, 2020)
Context: There is continuous search for therapeutic agents from indigenous plants that can be employed in the treatment of sickle cell anemia.